2021
DOI: 10.20525/ijrbs.v10i7.1424
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of Human Resource Information System (HRIS) usage in the health system of South Africa

Abstract: This systematic literature review is aimed at determining the predominance of existing studies conducted in HRIS as it relates to HRM, HRH, workforce management and the use of Information Systems (IS) and technology within the health sector. The main findings of the study demonstrate that HRIS benefits are the most researched at 11.8% with a) impact: implementation and IS in healthcare:10.5%; b) effectiveness: motivation, competence, workforce IS and adoption: 9.2%; c) workforce retention and migration: 7.9% d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 42 publications
4
13
0
Order By: Relevance
“…The study highlights that HRIS benefits have been a significant area of research, indicating the importance of HRIS in managing employees' digital records. This supports the argument that HRIS personnel records management is useful in keeping employees' correspondence records, as it aligns with the findings of existing literature on the benefits of HRIS in HRM and digital records (Udekwe et al, 2021).…”
Section: Usefulness Of Hris Personnel Records Management In Keeping E...supporting
confidence: 88%
See 2 more Smart Citations
“…The study highlights that HRIS benefits have been a significant area of research, indicating the importance of HRIS in managing employees' digital records. This supports the argument that HRIS personnel records management is useful in keeping employees' correspondence records, as it aligns with the findings of existing literature on the benefits of HRIS in HRM and digital records (Udekwe et al, 2021).…”
Section: Usefulness Of Hris Personnel Records Management In Keeping E...supporting
confidence: 88%
“…The above assertion corresponds with the findings by Udekwe et al (2021). In their study, HRIS was found to be beneficial in managing digital records within the human resource management (HRM) context.…”
Section: Usefulness Of Hris Personnel Records Management In Keeping E...supporting
confidence: 87%
See 1 more Smart Citation
“…Udekwe et al, [ 16 ] claim that providing a wide variety of information as an integrated database supports different sectors in providing critical connections across multiple departments/units and facilities, increasing the pace of information transfers. In addition to the preceding benefits, it is crucial to recognise a few of the limits of HRIS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An effective HRIS can be used by the healthcare sector to take actions relating to the standing of the healthcare workers in a country, which signifies the relevance of HRIS in the healthcare sector of a sustaining economy (Dida, 2021;Menant, Gilbert and Sauvezon, 2021;Sikira and Misheal, 2024). Appropriate incentives and financial support in the use of HRIS should be viewed as an imperative factor in the consciousness of an efficient and effective health workforce in general (Udekwe, Iwu, de la Harpe and Daramola, 2021b;Arakelian et al, 2022). Perhaps the healthcare sector is a substantial provider of the socioeconomic enhancement and well-being of a nation, and the deployment of HRIS in the healthcare sector will help do away with the obsolete approach to managing healthcare workers and improve the health and wellbeing of the country's population.…”
Section: Introductionmentioning
confidence: 99%